Representasi Serapan Bahasa Portugis sebagai Pemerkaya Kosakata Bahasa Indonesia - Fitriyah ZA, Mahmudah; Siddiq, Mohammad; V. Dekhnich, Olga (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2023)
Indonesian language is rich in loanwords. This is due to the historical presence of various colonizers in the country, such as the Netherlands, Portugal, England, and Japan. Additionally, there were trading interactions with nations like the Arabs, Indians, Chinese, and Persians. The influx of these foreign cultures inevitably left linguistic imprints on the Indonesian language. Portuguese, which arrived in 1511 with initial trading intentions, ended up being enticed into colonization, leading to the unwitting integration of Portuguese words into the Indonesian society. This research aims to examine the extent to which Portuguese words have been absorbed into the Indonesian language and have been used by the language users in this country without awareness. A qualitative method was employed in this study, relying on primary data gathered through direct interviews with native speakers of Portuguese. Secondary data was also collected through the analysis of various dictionaries. The findings of this research indicate that only a limited number of Portuguese words have been assimilated into the Indonesian language. Several words related to religious elements, food, and object names continue to be in use, such as "gereja" (church), "natal" (Christmas), "sekolah" (school), "bangku" (bench), and "kemeja" (shirt). This phenomenon can be attributed to the strong linguistic ties of the Indonesian society with religious and socio-cultural matters, as these loanwords have become deeply integrated and commonly used by the population.